Gene expression in grapevine cultivars in response to Bois Noir phytoplasma infection - Albertazzi, G.; Milc, J.; Caffagni, A.; Francia, E.; Roncaglia, E.; Ferrari, F.; Tagliafico, E.; Tagliafico, E.; Pecchioni, N.
Bois Noir phytoplasma is an emerging disease of Vitis vinifera in several regions of the world. No completely resistant grapevine cultivars are known and the physiology of disease remains still poorly understood so far. Affymetrix GeneChip1 oligonucleotide arrays have been used to identify differentially expressed genes between infected and recovered samples from Chardonnay and between infected and healthy samples from Manzoni Bianco. In the field, Manzoni showed reduced symptoms, while Chardonnay was highly susceptible to the disease. Results showed that expression levels of few hundreds genes were altered in infected plants, both common and specific for each cultivar, with effects on various metabolic pathways. In Chardonnay a serious inhibition of whole photosynthetic chain and photosystem I activity, Calvin-cycle enzymes transcription, lipid metabolism and phenylpropanoid biosynthesis was observed. Increasing physical barriers to limit phytoplsma spread in the plant was observed in infected Chardonnay and Manzoni plants, with the repression of genes responsible for cell wall degradation and the induction of genes involved in cell wall reinforcement. Interestingly, specifically in Manzoni the expression of a Myb transcription factor, belonging to a gene family that has a role in defense response, was induced. This is the first analysis of gene expression profiling in a grapevine-phytoplasma interaction using Affymetrix GeneChip1 array. Presented data provide an interesting picture of the transcriptional response of grapevine to Bois Noir and allowed the selection of several candidate genes for future functional analysis.
Keywords: VITIS VINIFERA; BOIS NOIR PHYTOPLASMA; AFFYMETRIX; GENE PROFILING; MICROARRAY